Semiconductor-thickness-dependent design of hetero-gate dielectric in double-gate TFETs - Nguyễn, Đăng Chiến (IEEE Publishing, 2024)
This study examined the dependence of the role and design of hetero-gate dielectric (HGD) on semiconductor film thickness in double-gate tunnel field-effect transistors (TFETs). The optimal position of the source-side dielectric heterojunction is nearly independent of the film thickness and aligned with the source-channel junction. The optimal position of the drain-side dielectric heterojunction is 7.5 nm for the films thicker than 70 nm and 9.25 nm for the films thinner than 20 nm. The on-current enhancement by the HGD engineering significantly decreases with scaling the film thickness, mostly because of the gradual disappear of the local potential well due to the increase of the double-gate coupling in scaled TFETs.